SWOT ANALYSIS FOR DEVELOPING COMPETITIVE ADVANTAGES FOR ONLINE FOOD BUSINESS VIA DIGITAL MARKETING - sari, rini kurnia; Sriwidadi, Teguh; Qanita, Aisyah (Bina Nusantara University, 2024)
Cencan Food, as an online food business that serves chicken dishes, snacks, and modern drinks, faces challenges in maintaining competitiveness in the increasingly competitive online food industry. This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) faced by Cencan Food, as well as formulate the right strategy to build competitive advantage through digital marketing. The SWOT analysis identified several key strengths of Cencan Food, such as the ability to adopt new technologies and the appeal of its products to various customer segments. However, several weaknesses found were inconsistencies in product quality and limitations in marketing resources. Key opportunities that can be utilized include increasing the use of social media and food delivery applications, while threats faced include intense competition and healthier food trends. The proposed strategies include menu diversification and implementation of a quality control system. Cencan Food can contribute to the Sustainable Development Goals (SDGs), especially for responsible consumption and production by prioritizing the use of sustainable raw materials and reducing food waste. Through this approach, Cencan Food is expected to strengthen its position in the market and achieve sustainable business growth. This study provides important insights for online food businesses in facing market challenges and taking advantage of digitalization opportunities.